Palladium (Pd): Properties, coordination chemistry and applications against cancer (Research, Society and Development, 2025)
The present manuscript consists of a review study concerning palladium(II) metal complexes aiming at their possible application in the fight against cancer. Since the advent of the so-called “cisplatin”, many efforts have been made to improve the results of the reference chemotherapy treatment of this “cisplatin” complex and its analogues and successors, such as second and third generation platinum complexes, among others. The physicochemical similarity between palladium and platinum, especially with respect to coordination chemistry, makes palladium complexes good candidates to replace and, eventually, surpass the quality of the therapeutic effects of platinum complexes. Therefore, the objective of this article is to discuss, through a bibliographic review, the fundamental aspects of the coordination chemistry of palladium (Pd) and its mechanism of action in biological media aiming at its use against various types of cancer, as a possible replacement for the classical platinum (Pt) complexes used against cancer cells. Finally, future perspectives for the applications of palladium (Pd) complexes in chemotherapy as an “anticancer agent” are presented.